Aspek Pemikiran Abu Al-Hasan Al-Syadzili (1196-1258): Aspects of Abu al-Hasan al-Shadhili’s Thought (1196–1258) - Syamsun Ni'am (Fenomena, 2004)
The 6th and 7th centuries Hijriyah saw the institutionalization of Sufism into formal orders (tarekat), yet the specific intellectual contributions of Abu Al-Hasan Al-Syadzili remain underexplored in contemporary scholarship. This study examines the core aspects of Al-Syadzili’s Sufi thought and their influence on Islamic mysticism. Using a qualitative library research method with descriptive-analytical and comparative approaches, the study analyzes primary sources, including Al-Syadzili’s teachings and related biographical works. The findings reveal that Al-Syadzili developed nine key doctrinal aspects, including dzikr, tafakkur, faqr, and ma’rifat, while firmly grounding his teachings in Sunni orthodoxy, distinguishing him from philosophical Sufis like Ibn ‘Arabi. The study concludes that Al-Syadzili successfully integrated shari’ah and spiritual reality, positioning the Syadziliyah order as a preserver of Sunni tradition. Recommendations include further comparative studies between Syadziliyah and other Sufi orders across different regions. Pada abad VI dan VII Hijriyah, tasawuf mengalami pelembagaan menjadi tarekat, namun kontribusi pemikiran Abu Al-Hasan Al-Syadzili belum banyak dikaji secara sistematis. Penelitian ini bertujuan mengidentifikasi aspek-aspek utama pemikiran tasawuf Al-Syadzili dan pengaruhnya terhadap dunia Islam. Menggunakan metode penelitian kepustakaan kualitatif dengan pendekatan deskriptif-analitis dan komparatif, penelitian ini menganalisis ajaran Al-Syadzili serta literatur biografis terkait. Hasil penelitian menunjukkan bahwa Al-Syadzili mengembangkan sembilan aspek doktrinal, antara lain dzikir, tafakur, fakir, dan makrifat, dengan tetap berpegang teguh pada tasawuf Sunni, berbeda dari sufi falsafi seperti Ibnu Arabi. Kesimpulannya, Al-Syadzili berhasil menggabungkan syariat dan hakikat, menjadikan tarekat Syadziliyah sebagai pelestari ortodoksi Sunni. Rekomendasi penelitian ini adalah perlunya studi komparatif antara tarekat Syadziliyah dengan tarekat lain di berbagai wilayah.